Effects of a 10-Week Exercise and Nutritional Intervention with Variable Dietary Carbohydrates and Glycaemic Indices on Substrate Metabolism, Glycogen Storage, and Endurance Performance in Men: A Randomized Controlled Trial - Anna Maria Moitzi; Martin Krššák; Radka Klepochova; Christoph Triska; Robert Csapo; Daniel König (SpringerOpen, 2024)
Abstract Background Daily nutrition plays an important role in supporting training adaptions and endurance performance. The objective of this 10-week study was to investigate the consequences of varying carbohydrate consumption and the glycaemic index (GI) together with an endurance training regimen on substrate oxidation, muscle energy storage and endurance performance under free-living conditions. Sixty-five moderately trained healthy men (29 ± 4 years; VO2 peak 55 ± 8 mL min−1 kg−1) were randomized to one of three different nutritional regimes (LOW-GI: 50-60% CHO with ≥ 65% of these CHO with GI < 50 per day, n = 24; HIGH-GI: 50-60% CHO with ≥ 65% CHO with GI > 70 per day, n = 20; LCHF: ≤ 50 g CHO daily, n = 21). Metabolic alterations and performance were assessed at baseline (T0) and after 10 weeks (T10) during a graded exercise treadmill test. Additionally, a 5 km time trial on a 400-m outdoor track was performed and muscle glycogen was measured by magnet resonance spectroscopy. Results Total fat oxidation expressed as area under the curve (AUC) during the graded exercise test increased in LCHF (1.3 ± 2.4 g min−1 × km h−1, p < 0.001), remained unchanged in LOW-GI (p > 0.05) and decreased in HIGH-GI (− 1.7 ± 1.5 g min−1 × km h−1, p < 0.001). After the intervention, LOW-GI (− 0.4 ± 0.5 mmol L−1 × km h−1, p < 0.001) and LCHF (− 0.8 ± 0.7 mmol L−1 × km h−1, p < 0.001) showed significantly lower AUC of blood lactate concentrations. Peak running speed increased in LOW-GI (T0: 4.3 ± 0.4 vs. T10: 4.5 ± 0.3 m s−1, p < 0.001) and HIGH-GI (T0: 4.4 ± 0.5 vs. T10: 4.6 ± 0.4 m s−1), while no improvement was observed in LCHF. Yet, time trial performance improved significantly in all groups. Muscle glycogen content increased for participants in HIGH-GI (T0: 97.3 ± 18.5 vs. T10: 144.5 ± 39.8 mmol L wet-tissue−1, p = 0.027) and remained unchanged in the LOW-GI and the LCHF group. At the last examination, muscle glycogen concentration was significantly higher in LOW-GI compared to LCHF (p = 0.014). Conclusion Changes in fat oxidation were only present in LCHF, however, lower lactate concentrations in LOW-GI resulted in changes indicating an improved substrate metabolism. Compared to a LCHF diet, changes in peak running speed, and muscle glycogen stores were superior in LOW- and HIGH-GI diets. The low GI diet seems to have an influence on substrate metabolism without compromising performance at higher intensities, suggesting that a high-carbohydrate diet with a low GI is a viable alternative to a LCHF or a high GI diet. Trial registration: Clinical Trials, NCT05241730. https://clinicaltrials.gov/study/NCT05241730 . Registered 25 January 2021.